Evaluasi Strategi Pemasaran Melalui Analisis Swot pada Usaha Vouin Dafsa - Lisa, Lisa; Beni, Sabinus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Business is a word that we often hear in every conversation between people who are carrying out various activities. Business can be interpreted as a business in the world of trade or a certain business field. Business in general terms can be interpreted as an activity or activity which includes activities such as: producing goods/services, distributing goods/services, then selling them to consumers whose goods/services are useful for their daily lives. The aim of this research is to find out a picture of the implementation of the Dafsa Vouin business before and after a SWOT analysis. This type of research is qualitative with an individual interview method. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people or observable behavior. Data collection was carried out by the author directly from the original source or location where the research was carried out, up to finding ways to obtain it. The following are the results of interviews that have been answered by respondents with marketing strategies that have been carried out by business actors in providing services and promoting Vouin Dafsa businesses to consumers. Based on the research results that have been obtained, it can be concluded that there are several strategies used, namely SWOT analysis to improve the Vouin Dafsa business